2021
DOI: 10.48550/arxiv.2103.16477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uniqueness of ad-invariant metrics

Diego Conti,
Viviana del Barco,
Federico A. Rossi

Abstract: We consider Lie algebras admitting an ad-invariant metric, and we study the problem of uniqueness of the ad-invariant metric up to automorphisms. This is a common feature in low dimensions, as one can observe in the known classification of nilpotent Lie algebras of dimension ≤ 7 admitting an ad-invariant metric. We prove that uniqueness of the metric on a complex Lie algebra g is equivalent to uniqueness of ad-invariant metrics on the cotangent Lie algebra T * g; a slightly more complicated equivalence holds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
(74 reference statements)
2
6
0
1
Order By: Relevance
“…In particular, real nilpotent Lie algebras with an ad-invariant metric are classified up to dimension 10 in [15]. In [5], we showed that the irreducible Lie algebras appearing in this classification admit a unique ad-invariant metric (up to sign); as a step in the proof, we proved that all of them are nice. Nice Lie algebras possess a strong algebraic structure, which can be encoded in a special kind of directed graph.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In particular, real nilpotent Lie algebras with an ad-invariant metric are classified up to dimension 10 in [15]. In [5], we showed that the irreducible Lie algebras appearing in this classification admit a unique ad-invariant metric (up to sign); as a step in the proof, we proved that all of them are nice. Nice Lie algebras possess a strong algebraic structure, which can be encoded in a special kind of directed graph.…”
Section: Introductionmentioning
confidence: 89%
“…Proof. Nilpotent Lie algebras of dimension ≤ 10 admitting ad-invariant metrics were classified by Kath in [15] and they were shown to be nice in [5] (see Table 1…”
Section: Nonnice Lie Algebras With An Ad-invariant Metric In Low Dime...mentioning
confidence: 99%
See 3 more Smart Citations